2019
DOI: 10.1103/physrevd.99.045006
|View full text |Cite
|
Sign up to set email alerts
|

Goldstone bosons and the Englert-Brout-Higgs mechanism in non-Hermitian theories

Abstract: In recent work Alexandre, Ellis, Millington and Seynaeve have extended the Goldstone theorem to non-Hermitian Hamiltonians that possess a discrete antilinear symmetry such as P T and possess a continuous global symmetry. They restricted their discussion to those realizations of antilinear symmetry in which all the energy eigenvalues of the Hamiltonian are real. Here we extend the discussion to the two other realizations possible with antilinear symmetry, namely energies in complex conjugate pairs or Jordan-blo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 49 publications
0
71
2
Order By: Relevance
“…While in the former proposition Noether's theorem is evaded the latter is based on the standard variational principle leading to standard Noether currents. Moreover with regard to the Higgs mechanism the "surface term approach" predicts that the gauge particle becomes massive in the local case [20], whereas the "pseudo-Hermitian approach" leads to a theory in which the gauge particle remains massless at the exceptional point [18]. Here we also find that the explicit form of the Goldstone bosons differs.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…While in the former proposition Noether's theorem is evaded the latter is based on the standard variational principle leading to standard Noether currents. Moreover with regard to the Higgs mechanism the "surface term approach" predicts that the gauge particle becomes massive in the local case [20], whereas the "pseudo-Hermitian approach" leads to a theory in which the gauge particle remains massless at the exceptional point [18]. Here we also find that the explicit form of the Goldstone bosons differs.…”
Section: Introductionmentioning
confidence: 65%
“…So far two distinct alternative propositions have been made to overcome this issue. Alexandre, Ellis, Millington and Seynaeve proposed to apply a non-standard variational principle by keeping some non-vanishing surface terms [17,20] or, in line with the pseudo-Hermitian/PT -symmetric quantum mechanical approach [24,25,26,27], one may seek a consistent equivalent similarity transformed Hermitian action, as pursued by Mannheim and the present authors [18,19]. While some features are the same in both approaches, e.g.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has also been suggested that non-Hermitian quantum field theory might also have applications in fundamental physics, e.g., to neutrino physics [8][9][10], dark matter [11] Higgs decays [12] and particle mixing [13]. It has been shown that it is possible to carry over to PT -symmetric non-Hermitian theories familiar concepts from Hermitian quantum field theory such as the spontaneous breaking of global symmetries [14][15][16] and the Englert-Brout-Higgs mechanism in gauge theories [17][18][19], despite the appearance of subtleties [20,21] in the relationship between current conservation, Lagrangian symmetries and Noether's theorem [22] in PT -symmetric theories.…”
Section: Introductionmentioning
confidence: 99%